The Influence of the Recruitment Process on PT Pos Indonesia's Employee Performance - NURHAYANA NURHAYANA (Husnayain Business Review, 2022)
This study aims to determine the effect of the recruitment process on employee performance of PT Pos Indonesia (Persero) Sudirman Pekanbaru. In analyzing the data obtained from the Respondents 64 people. The data calculated used SPSS version 23. Result of t-test obtained that the value of t-count is greater than the value of t-table, then there is the influence of recruitment variables on employee performance at PT Pos Indonesia (Persero) Sudirman Pekanbaru, Indonesia. Then Coefficient of Determination Test showed value of 0.509 means  that 50.9% percentage contribution of independent variables to the dependent variable is the recruitment of employee performance. where remaining 49.1% influenced by other variables not included in this study.